Phonemic Characterization of the Production of English Consonants by Nonnative Saudi Speakers - Algethami, Ghazi (International Journal of Language and Literary Studies, 2022)
The current study characterizes the production of English consonants by Saudi L2 speakers and offers pedagogical implications for teachers and curriculum designers. Fifteen nonnative Saudi speakers, with at least one of year of residence in an English-speaking country, were recorded individually reading an English passage containing all the English consonants. Their recordings were subjected to a segmental, phonemic analysis to identify and describe any phonemic mispronunciation. The following consonants were found challenging to the Saudi L2 speakers: /v/, /?/, /p/ and /?/. Their production of these consonants was characterized by devoicing of /v/, inserting /g/ after /?/, voicing or lack of aspiration of /p/, and trilling or tapping of /?/. L1 influence played the main role in their mispronunciation. Their production of /v/ and /p/ resulted in phonemic substitutions with /f/ and /b/, respectively. These substitutions have the potential of being detrimental to speech intelligibility according to the Functional Load Principle and Lingua Franca Core; therefore, they should be prioritized in teaching English pronunciation to Saudi learners. The paper concludes by outlining pedagogical implications and offering tips for teaching English pronunciation to Saudi learners.